Multi-scale partnerships for tropical forest governance - Sergio Rosendo (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2004)
This paper aims to contribute to the understanding of partnerships for the conservation and sustainable use of tropical forests involving various stakeholders at different levels or scales. It focuses on extractive reserves in Brazilian Amazonia and the partnerships and interactions that have evolved between local populations and NGOs (national and international), government agencies and international donors for their creation, implementation and management. Extractive reserves are protected areas designated for the sustainable use of natural resources by the resident population. They aim to achieve multiple goals including conserving biodiversity, satisfying the basic needs of the population and strengthening social organisation as a means to guarantee their participatory management. The paper concludes that partnerships have played an important role in the formal creation of extractive reserves as a new management regime relying on collective action between individuals and organisations. However, it also argues that different actors become involved in extractive reserves as a means to achieve different goals, which are not always complementary or even compatible. Partnerships are affected by a number of unconstructive dynamics and incentive structures, which emerge when there are significant power inequalities between the different actors, including inequalities related to access to financial resources.
Keywords: 330; access rights; Brazilian Amazonia; co-management; extractive reserves; partnerships; Forstökonomie; Forstpolitik; Nachhaltige Entwicklung; Nichtregierungsorganisation; Projektmanagement; Kooperation; Tropischer Regenwald; Brasilien